Defining issue of thermal comfort control through urban masjid facade design - Abdullah, Fauziah Hanum; Abdul Majid, Noor Hanita; Othman, Rosniza (Elsevier, 2016)
Urban masjids should be provided with an acceptable thermal comfort for worshippers to feel comfortable and relaxed to attain a feeling of tranquility, peace and serenity. This paper aim is to define the issues related to thermal comfort control through urban masjid facade design to achieve the quality of life. The methodology for the study is analytical review to define theoretical framework related to the key areas. The results indicated that healthy indoor living, quality of life in the urban environment, energy consumption and implementation of passive design strategies are the issues governing thermal comfort through the design of facade for urban masjid.